PENINGKATAN SUHU MODUL DAN DAYA KELUARAN PANEL SURYA DENGAN MENGGUNAKAN REFLEKTOR - -, Ihsan (Fakultas Sains dan Teknologi UIN ALauddin, 2013)
Research has been carried out with the title: An increase temperature and output power the solar panels by using reflectors. This study aimed to determine the effect of the reflector mounting solar panels to temperature and output power. Data collection was divided into two phases of data collection at the solar panel without reflector and retrieval of data on a panel by using reflectors. Corner reflector was varied from 10o to 80o. The results showed that under normal conditions (not cloudy), the addition of reflectors on the solar panel causing an increase in the intensity of sunlight on the surface of the panel. Increase in temperature causes an increase in the intensity of the module. Module temperature increase causes an increase in output power.Keywords: Module temperature, output power, solar panels, reflectors